The problem of preserving the mother tongue of Tuvans of China - Yusha, Zhanna M. (The New Research of Tuva, 2018)
Article analyzes the modern language situation, relevant for Tuvans in China in the conditions of diverse ethnic community and multilingualism. Mother tongue for Tuvans in China is Tuvan. Chinese Tuvan is considered one of the foreign dialects of modern Tuvan language. Up to the present time this native language has been spoken orally without a national written language. The article characterizes the status of Tuvan language, defines its functions, level of language competence and speech culture of Chinese Tuvans and analyzes the problems of preservation of the mother tongue. Article exposes the four zones of distribution of Tuvan language and reveals the relation between the functionality of Tuvan speech and the region of residence, economic and cultural type and age of native speakers. The lexical and phonetic features relevant for the dispersed groups are determined. The current educational system for Tuvan children, who are taught in Mongolian or Kazakh schools, is briefly described. Tuvans, being in the multilingual environment, are natural polylingua. They, in addition to their native language, have a good command of others (Mongolian and Kazakh), and allow language changes in their native speech tracing back to interactions with the languages of neighboring peoples. This possibly can be one of the initial signs of the loss of their native language. The processes of language interference occurring in the speech of carriers of Tuvan language are shown under the influence of the languages of neighboring, numerically exceeding peoples. The role of the mobile phone and the Internet in the modern life of the Tuvans is described. Tuvan users of mobile communications transmit voice messages in their mother tongue, and written messages - in Chinese with hieroglyphics. If Uighurs and Kazakhs have developed computer keyboard programs in their native language, Tuvans are leaking this possibility and are forced to write and read only in other languages, which conduces to the assimilation of mother tongue. Article also describes expanding role of Chinese language as interethnic mean of communication in context of ethnotourism development on the territory of Tuvans. Children are trended to learn only the Chinese language ignoring their mother tongue. The problem of development and preservation of the mother tongue by the Chinese Tuvans is analyzed in the context of diverse ethnic environment. Author assumes this problem can only be solved at the government level, within the framework of cooperation between Russia and China in the field of education.